Physical properties of graphene / Mohd Rafal Sahudin ... [et al.] - Sahudin, Mohd Rafal; Zourob, Muhammed; Noor Akashah, Muhammad Haziq; Abdul Rani, Rozina; Makhsin, Siti Rabizah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
In the realm of engineering materials, a profound understanding of structural and physical characteristics holds paramount importance due to their ubiquitous presence and diverse applications. This comprehensive review delves deeply into the intricate physical attributes, commonly referred to as "physical properties," of materials based on graphene. It encompasses a wide range of aspects, including magnetic properties, optical behaviours, electrical and thermal conductivities, thickness and layer arrangements, size and shape variations, colour properties, melting points, and hardness traits. This review also explores the intriguing correlation between graphene's thickness and layering and their respective effects on its properties. Special emphasis is placed on the characterization techniques used to unveil these properties, with detailed examples from recent literature illustrating their significance. Advanced instrumentation, such as Atomic Force Microscopy (AFM), Surface Plasmon Resonance spectroscopy (SPR), Raman spectroscopy, Transmission Electron Microscopy (TEM), and X-ray Diffraction (XRD), is harnessed to provide comprehensive insights into the physical characteristics of graphene-based materials. In essence, this concise yet comprehensive review illuminates the exceptional physical properties of graphene-based materials and their potential to revolutionize various industrial sectors.